2016
DOI: 10.1021/acs.analchem.6b04564
|View full text |Cite
|
Sign up to set email alerts
|

Sheathless Focusing and Separation of Diverse Nanoparticles in Viscoelastic Solutions with Minimized Shear Thinning

Abstract: Viscoelastic microfluidics becomes an efficient and label-free hydrodynamic technology to enrich and separate micrometer-scale particles, including blood cells, circulating tumor cells, and bacteria. However, the manipulation of nanoscale particles by viscoelastic microfluidics remains a major challenge, because the viscoelastic force acting on the smaller particle decreases dramatically. In contrast to the commonly used polymer solutions of high molecular weight, herein we utilize the aqueous solutions of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…7d) and k-DNA molecules in the flow of PEO solution with a molecular weight of 0.6 MDa through a double-spiral microchannel. They observed a decreasing focusing efficiency with the increase of PEO molecular weight (up to 4 MDa) [28].…”
Section: Rectangular Microchannelsmentioning
confidence: 96%
See 3 more Smart Citations
“…7d) and k-DNA molecules in the flow of PEO solution with a molecular weight of 0.6 MDa through a double-spiral microchannel. They observed a decreasing focusing efficiency with the increase of PEO molecular weight (up to 4 MDa) [28].…”
Section: Rectangular Microchannelsmentioning
confidence: 96%
“…They also proposed a six-stage process model to explain the observed particle focusing process in Deancoupled elasto-inertial flows. In a recent study Liu et al [28] demonstrated a high-quality focusing of various nanoparticles in PEO solutions of low molecular weight that can offer sufficient elastic forces while at minimized shear thinning effects. They achieved an over 80% focusing efficiency for both 100 nm diameter PS particles (Fig.…”
Section: Rectangular Microchannelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For PEO solutions of low concentrations (c < 0.19 wt %, the overlapping concentration for PEO of 600 kDa 13 ), η p and λ can be expressed as 0. U, indicating that the particle trajectory is predominately dependent on the particle size, PEO concentration, and flow speed.…”
Section: Resultsmentioning
confidence: 99%